Studies on ferns of Lesser Sunda Islands II: An enumeration on the ferns of Bali - Lestari, Wenni Setyo; Wardani, Wita; Muhaimin, Muhamad; Iskandar, Eka Aditya Putri; Windadri, Florentina Indah; Haerida, Ida; Nadhifah, Ainun; Praptosuwiryo, Titien Ngatinem; Hidayat, Arief; Adjie, Bayu (Phytotaxa, 2025)
An updated and annotated checklist on the ferns of Bali is presented, based on data from living collections, herbarium specimens, and field surveys. A total of 216 species were identified, representing 102 genera and 30 families. Pteridaceae with 12 genera and 33 species was the most species-rich family, followed by Polypodiaceae comprising 14 genera and 32 species. Asplenium was the most diverse genus, with 13 species, followed by Adiantum with eight species. Among the recorded taxa, 18 species are reported here as new records for Bali Island.